Proposal of a novel cardiovascular risk prediction score in lupus nephritis - Molnár, Adél; Juha, Márk; Bulajcsík, Klaudia; Tabák, Ádám Gy.; Tislér, András; Ledó, Nóra (Frontiers in Immunology, 2024)
Introduction: Patients with systemic lupus erythematosus are prone to develop cardiovascular disease (CVD), and have increased morbidity and mortality. Methods: We conducted a retrospective analysis on lupus nephritis patients to assess the occurrence and predictors of major adverse cardiovascular events (MACE). Data were collected from patients who underwent kidney biopsy between 2005 and 2020. Statistical analysis was performed to unveil correlations. Results: 91 patients were analyzed in this period, with a mean age of 37.3±12.3 years and 86% being female. The mean follow-up time was 62±48 months. 15.38% of the patients underwent at least one MACE. Two patients deceased of CVD. Increased age (35.81±11.14 vs 45.5±15.11, p=0.012) entailed a higher occurrence of MACEs. Neutrophil count (5.15±2.83 vs 7.3±2.99, p=0.001) was higher, whereas diastolic blood pressure (DBP) was lower (89.51±10.96 vs 78.43±6.9, p<0.001) at the time of the biopsy in patients with MACE. Age, neutrophil count, and DBP proved to be independent predictors of MACEs. We propose a new model (CANDE -Cardiovascular risk based on Age, Neutrophil count, and Diastolic blood pressure Estimation score) calculated from these variables, which predicts the probability of MACE occurrence. Conclusion: This study underscores the importance of actively screening for cardiovascular risks in this vulnerable patient population. Age, neutrophil count, and diastolic blood pressure have been established as independent risk factors for MACE in lupus nephritis. The CANDE score derived from these parameters may serve as a prompt, cost-effective, and easily accessible estimation tool for assessing the likelihood of major adverse cardiovascular risk. These findings emphasize the necessity for comprehensive management strategies addressing both immune dysregulation and cardiovascular risk factors in systemic lupus erythematosus to mitigate adverse outcomes.